Depressive symptoms in Chinese family caregivers of patients with heart failure: A cross-sectional study. Issue 13 (March 2017) - Hu, Xiaolin; Huang, Wenxia; Su, Yonglin; Qu, Moying; Peng, Xingchen
Abstract : Abstract: Depressive symptoms are related to negative health outcomes in caregivers of patients with HF. Understanding the factors that are associated with depressive symptoms among caregivers is essential to providing appropriate interventions. Little is known about which status and factors are related to depressive symptoms among Chinese caregivers of patients with heart failure. This study aimed to investigate the status of depressive symptoms and to identify the factors that are associated with depressive symptoms in family caregivers of patients with heart failure in China. A cross-sectional design and a convenience sample were used. Participants (N = 134) from 1 hospital in Chengdu were recruited from June 2013 to June 2014. The following measurement tools were used in this study: Center for Epidemiologic Studies Depression Scale, Hospital Anxiety and Depression Scale, Coping Strategies Simplified Coping Style Questionnaire, and Zarit Burden Interview. A hierarchical multiple linear regression analysis was used to determine which factors were associated with depressive symptoms. The results showed that 31% of the caregivers experienced depressive symptoms. The type of payment for treatment ( b = −0.312, P < 0.01), readmissions within the last 3 months ( b = 0.397, P < 0.01), duration of caregiving ( b = −0.213, P < 0.05), caregiver burden ( b = 0.299, P < 0.05), active coping ( b = −0.235, P < 0.01), and negative coping ( b = 0.245, P < 0.05) were related to caregivers' depressive symptoms. Fifty-four percent of the variance in caregivers' depressive symptoms was explained by these factors. The caregiver depressive symptoms in China were higher than those reported in studies that were conducted in Western countries. Caregiver depressive symptoms can be improved by providing support for new caregivers (with a caregiving duration of less than 1 year), reducing readmissions, easing caregiver burden, and promoting their coping strategies.